Performance assessment of service differentiation in IEEE 802.11e Wireless LANs. (14th January 2008) - Hwang, I-Shyan; Wu, Jheng-Han
This paper proposes a performance assessment scheme for service differentiation provisioning for IEEE 802.11e EDCF. The analytical model is developed based on queueing theory to derive the state probabilities and transition probabilities, and the mean waiting time and loss probability of those two queues. It is expected that our scheme not only provide the QoS of real-time traffic but also not sacrifice the non real-time traffic. The network performance of the queueing model is validated and compared by simulation in terms of mean waiting time and loss probability. The established mathematical model can be extended to the existing four queues models.